2022
DOI: 10.3389/fendo.2022.815835
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and Age-Associated Differences in Bone Marrow Adipose Tissue and Bone Marrow Fat Unsaturation Throughout the Skeleton, Quantified Using Chemical Shift Encoding-Based Water–Fat MRI

Abstract: Bone marrow adipose tissue (BMAT) is a dynamic tissue which is associated with osteoporosis, bone metastasis, and primary bone tumors. The aim of this study is to determine region-specific variations and age- and gender-specific differences in BMAT and BMAT composition in healthy subjects. In this cross-sectional study, we included 40 healthy subjects (26 male: mean age 49 years, range 22–75 years; 14 female: mean age 50 years, range 29–71) and determined the bone marrow signal fat fraction and bone marrow uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…The largest difference between FA species in the regulated versus constitutive marrow sites was seen in the 18:1 to 18:0 unsaturation ratio (4.40 versus 7.91, p=0.007), and the 16:1 versus 16:0 unsaturation ratio (0.11 versus 0.19, p=0.031) (Figure 7B-C). We thus conclude that human BM samples from a rBMAd-rich site in the context of BM remodeling driven by hematopoietic demand present a lower unsaturation ratio, as measured by 16:1/16:0 -and 18:1/18:0-FA content, than samples obtained from a cBMAd-rich site, which complements previously reported results for rabbit and rats marrow at steady-state (1,3335) as summarized in Table 1.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The largest difference between FA species in the regulated versus constitutive marrow sites was seen in the 18:1 to 18:0 unsaturation ratio (4.40 versus 7.91, p=0.007), and the 16:1 versus 16:0 unsaturation ratio (0.11 versus 0.19, p=0.031) (Figure 7B-C). We thus conclude that human BM samples from a rBMAd-rich site in the context of BM remodeling driven by hematopoietic demand present a lower unsaturation ratio, as measured by 16:1/16:0 -and 18:1/18:0-FA content, than samples obtained from a cBMAd-rich site, which complements previously reported results for rabbit and rats marrow at steady-state (1,3335) as summarized in Table 1.…”
Section: Resultssupporting
confidence: 89%
“…In recent years, primary rat cBMAds from tail vertebrae and distal tibia were likewise shown to contain a higher proportion of unsaturated fatty acids in caudal vertebrae or distal tibia as compared to rat rBMAds isolated from either lumbar vertebrae or femur plus proximal tibia combined (1). Congruently MRI, 1 H-MRS, and gas chromatographic data from human subjects consistently showed that BM adipose tissue (BMAT) from sites of red marrow contained highly saturated lipids, compared to the mostly unsaturated lipids detected at yellow marrow sites (1, 3335). From murine samples, it is considerably more challenging to obtain sufficient BMAT for analysis due to the size of the animal as well as the amount of BMAT present in the bones (32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beekman et al (27) studied the sex differences in bone marrow fat and found that age was significantly associated with spinal bone marrow fat only in men. Bone marrow adipocytes are a tissue associated with a variety of skeletal diseases, such as osteoporosis and bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…With age, in both men and women, the ratio of VAT over SAT increases with the accumulation of VAT [ 21 ]. Aging is also associated with an accumulation of bone marrow AT [ 22 ] with a reversion of sex differences and discrete age- and gender-specificity according to bone location [ 23 ].…”
Section: Sex Differences In Fat Depots In Lifespan and Agingmentioning
confidence: 99%